Evaluation of Rhode Island's Family Independence Program, May 1996 - April 2000 - Ann Dryden Witte; Magaly Queralt; Helen Tauchen (Wellesley College, Department of Economics, 2001)
We assess the impact of Rhode Island's Family Independence Program (FIP) on the employment and earnings of current and former cash assistance recipients. We use administrative data from many sources, including data from state cash assistance records and from employer reports of employment and earnings from the Unemployment Insurance program. Our data are for all-female-headed households receiving Rhode Island cash assistance during the period May 1996 to April 2000. In all we have observations on 29,253 families for an average of 16.6 quarters. We estimate our models using a number of techniques and find that the impacts of major variables are robust across the techniques used. Our results indicate that the major impact of FIP was to increase the likelihood that current and former cash assistance recipients would work. Our best estimate is that the impact of the many changes associated with FIP was to increase the likelihood of work by about 10%. Estimates also indicate that FIP increased the quarterly earnings of current and former cash assistance recipients. However, the estimated increase in quarterly earnings due to FIP was relatively modest (i.e., about 200 per quarter). During the study period, earnings increased substantially (i.e., from a little over 1,000 per quarter to over 2,500 per quarter), but our results indicate that most of this increase was due to increases in the Rhode Island minimum wage, not to FIP.
Keywords: I38; J22; I20; H40; 330; Welfare Reform; Child Care; Medicaid; Minimum Wage; Employment and Earnings; Familienleistungsausgleich; Familienpolitik; Rhode Island